THE CRISIS’ EFECTS ON THE STOCK OF ROMANIAN HUMAN CAPITAL - Diaconu Laura; Popescu Cristian (Annals of the University of Oradea: Economic Science, 2009)
The knowledge, skills and abilities, as main aspects of human capital, have significant influences on the economic development of a country. Unfortunately, in Romania, the low level of human capital at the young people, combined with one of the Europe’s l